Stress-induced hyperglycaemia and venous thromboembolism following total hip or total knee arthroplasty - Cohn, Danny M.; Hermanides, Jeroen; DeVries, J. Hans; Kamphuisen, Pieter-Willem; Kuhls, Silvia; Homering, Martin; Hoekstra, Joost B. L.; Lensing, Anthonie W. A.; Büller, Harry R. (Thrombosis and Haemostasis, 2012)
Stress-induced hyperglycaemia is common during orthopaedic surgery. In addition, hyperglycaemia activates coagulation. The aim of the study was to assess whether stress-induced hyperglycaemia is associated with symptomatic or asymptomatic venous thromboembolism (VTE) following orthopaedic surgery. We performed post-hoc analyses in the four RECORD studies (REgulation of Coagulation in major Orthopaedic surgery reducing the Risk of Deep venous thrombosis and pulmonary embolism). Separate analyses were performed for patients undergoing elective total hip or knee replacement. Outcome measures were symptomatic VTE and “total VTE” (defined as the composite of symptomatic VTE, asymptomatic DVT assessed by per protocol venography and all cause mortality). Glucose levels were measured pre-op and 6 hours post-op, categorised into quartiles, based on the distribution in the respective cohorts. The influence of glucose, adjusted for body mass index, age, gender and diabetes mellitus on VTE was assessed by logistic regression analyses. A total of 12,383 patients were eligible for assessment of symptomatic VTE, and 8,512 patients were eligible for assessment of total VTE. Increased glucose levels after total hip replacement were associated with total VTE; adjusted odds ratio (OR) highest versus lowest quartile 1.9 (95% confidence interval [CI] 1.3 to 3.0). Furthermore, increase in glucose levels during total hip replacement was associated with total VTE (OR highest versus lowest quartile 1.8 (95%CI 1.2 to 2.8). This was not observed in patients undergoing total knee replacement, probably due to differences in the applied surgical procedures.
Keywords: Venous thromboembolism; deep venous thrombosis; pulmonary embolism; hyperglycaemia; arthroplasty